2021
DOI: 10.1002/ecy.3536
|View full text |Cite
|
Sign up to set email alerts
|

Benthic micro‐ and macro‐community succession and coral recruitment under overfishing and nutrient enrichment

Abstract: Herbivory and nutrient availability are fundamental drivers of benthic community succession in shallow marine systems, including coral reefs. Despite the importance of early community succession for coral recruitment and recovery, studies characterizing the impact of top‐down and bottom‐up drivers on micro‐ and macrobenthic communities at scales relevant to coral recruitment are lacking. Here, a combination of tank and field experiments were used to assess the effects of herbivore exclusion and nutrient enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…In the context of resilience‐based management, actions should be taken to reduce the negative effects of nutrients and sediment loads from the Fiherenana and Onilahy rivers that have increased due to unmanaged mining and agricultural and deforestation activities (Bruggemann et al., 2012; Sheridan et al., 2014). These actions are critical as coral recruits are particularly sensitive to increasing levels of sedimentation (Brunner et al., 2021; Wakwella et al., 2020) and nutrients (D'Angelo & Wiedenmann, 2014; Evensen et al., 2021). Moreover, privileging better land and watershed management actions will also improve water quality and coral reef health to the benefit of other reef communities.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of resilience‐based management, actions should be taken to reduce the negative effects of nutrients and sediment loads from the Fiherenana and Onilahy rivers that have increased due to unmanaged mining and agricultural and deforestation activities (Bruggemann et al., 2012; Sheridan et al., 2014). These actions are critical as coral recruits are particularly sensitive to increasing levels of sedimentation (Brunner et al., 2021; Wakwella et al., 2020) and nutrients (D'Angelo & Wiedenmann, 2014; Evensen et al., 2021). Moreover, privileging better land and watershed management actions will also improve water quality and coral reef health to the benefit of other reef communities.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, rubble fragments may have supported more complex and/or well-developed biofilms than the artificial discs, leading to the presence of stronger induction cues. Indeed, the presence of complex microhabitats likely created pockets of unique biofilm communities 83 85 that may have offered a wider diversity of potential inducers. It is also likely that biofilm discs supported early successional species (+4 weeks conditioned) 83 that were less mature and inductive than those on rubble fragments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to preemption, early colonists often modify the environment in ways that favor their persistence, creating feedbacks that can inhibit new colonizers (Connell & Slatyer, 1977 ; Orrock et al, 2008 ; Peterson, 1984 ; Yelenik & D'Antonio, 2013 ). Large numbers of studies have shown that abundant algae can inhibit coral recruitment by preempting space and by creating an environment that is hostile to coral colonists (e.g., Bulleri et al, 2018 ; Evensen et al, 2021 ; Hughes et al, 2007 ; Mumby et al, 2016 ; Schmitt et al, 2021 ). In particular, the dominant alga that proliferated under reduced herbivory conditions in our study, the creeping foliose brown alga Lobophora , can inhibit coral recruitment by suppressing the settlement of coral larvae (Baird & Morse, 2004 ; Evensen, Doropoulos, Morrow, et al, 2019 ; Evensen, Doropoulos, Wong, et al, 2019 ; Kuffner et al, 2006 ; Morrow et al, 2017 ) and by killing newly settled corals via overgrowth and allelopathy (Evensen, Doropoulos, Wong, et al, 2019 ; Johns et al, 2018 ; Rasher & Hay, 2010 ).…”
Section: Discussionmentioning
confidence: 99%